Understanding the gas phase formation of silicon carbide during reactive melt infiltration of carbon substrates - Manikanda Priya Prakasan; Tobias Schneider; Dietmar Koch (Open Ceramics)
Carbon-Carbon composites with protective Silicon Carbide surface (C/C-SiC) are well-known for their exceptional heat and oxidation resistance. Reactive Melt Infiltration (RMI) is employed to impart oxidation resistance to these composites by transforming the carbon matrix surface into silicon carbide. Successful infiltration yields dense-grey SiC, while unsuccessful process yields porous-green layer, compromising oxidation resistance and inducing high-temperature surface damage. Identifying the causes of failed siliconization and their influencing factors is crucial for enhancing high-temperature performance. This study proves that SiC formation from gas-phase reactions prior to silicon melting causes green surface layer. Through siliconization experiments and Thermogravimetric Analysis combined with Fourier Transform Infrared spectroscopy, these gaseous reactions are linked to the specific-surface characteristics of silicon powder used. Microstructural differences between gas and liquid reaction-formed SiC leads to the proposed four-step reaction pathway, explaining the formation of green SiC. These findings offer vital insights for optimizing the outcome of surface siliconization process.